Effects of prior exhaustive leg or arm exercise on subsequent performance, power and EMG activity in a different muscle group - Gabe Beltrami, F.; de Groot, R.; Rauch, L.; Tucker, R.; Rae, D. E.; Noakes, T. D. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
A prior bout of exhaustive exercise is known to result in early exhaustion being reached during a subsequent bout of maximal exercise. Much of the research to date has examined peripheral factors for this phenomenon. Therefore, the aim of this study was to investigate the contribution of central regulation on the performance of maximal exercise preceded by a bout of exhaustive exercise using a different muscle group. Methods: Ten healthy men (5 well-trained cyclists and 5 well-trained canoeists) were recruited for this study and all completed two exercise trials. In trial 1, subjects performed an incremental leg ergometry test to exhaustion (LEG A), followed 15 minutes later by an incremental arm ergometry test to exhaustion (ARM B). In trial 2, the order was reversed (ARM A followed 15 minutes later by LEG B). The two trials were separated by at least 3 days and the order in which the subjects performed the trials was randomised. Time to exhaustion (TE), power output (PO), heart rate (HR), rating of perceived exertion (RPE), oxygen consumption (VO2), ventilation rate (VE), plasma lactate (LA) and electromyography (EMG) of two lower (rectus femoris and vastus lateralis) and two upper limb (triceps and biceps) muscles were measured during all trials. Results: During the A trials, subjects reached exhaustion faster and at a higher PO during legs compared to arms. While HR and RPE were similar in the leg and arm tests at exhaustion, VO2 (p = 0.018) and VE (p = 0.008) were lower in the arm test. Performance during ARM B was unaffected by prior LEG A. However, prior ARM A significantly reduced TE (p = 0.011) and peak PO (p = 0.011) during subsequent LEG B. There were no changes in maximal VO2, HR, RPE, VE and LA between trials A and B of each muscle group. LA was higher at the beginning of LEG B (p < 0.001) and ARM B (p = 0.001) exercise compared to their respective A trials. Prior LEG A affected subsequent ARM B HR for the first 40% of the trial. During LEG B, however, HR differed only at the start and 20% of the test. EMG increased linearly during all the trials and maximal EMG activity measured during the tests was only 55% of previous MVC. RPE rose linearly during all tests, regardless of different levels of LA and HR. None of the measured physiological/neuromuscular variables measured showed a plateau at exhaustion. Conclusion: Prior arm exercise reduced peak power output during a subsequent bout of exhaustive leg exercise without altering the physiological or EMG variables measured in this study. In contrast, prior leg exercise did not alter peak power output during subsequent arm exercise. These results suggest that during the tests RPE was set in anticipation, being independent of the amount of muscle mass activated, HR or LA. These data are difficult to interpret according to traditional peripheral models of exercise fatigue and deserves further investigations.